Disavowing Disability Richard Baxter and the Conditions of Salvation - McKendry, Andrew (Humanities, 2021)
Examines the role that disability, both as a concept and an experience, played in seventeenth-century debates about salvation and religious practice. This title is also available as Open Access on Cambridge Core.